Letter (copy) : Help for the Workers of Spain Fund - Tewson, Vincent
1937-01-06 -2- The Fund is administered by a Joint Committee of the I.F.T.U. and the L.S.I. who have direct contact with a Committee representative of the industrial and political movements in Spain. The Committee in Spain informs the Joint International Committee of the commodities which are required and acts as the receiver of the goods sent which are then distributed to the best possible advantage. We have, however, made large contributions to ambulance units. The Spanish Medical Aid Committee's Unit has been on the Northern front and the Scottish Ambulance Unit has actually been located in Madrid. We are, at the moment, preparing a detailed statement on this matter and when it is printed I will see that you get a copy. If there is any more specific information you desire please drop me a line. Yours sincerely, Assistant Secretary. 292/946/28/118(ii)